Inadequately employed terms in leprosy - Neyra Ramírez, José (2008)
Leprosy is a transmissible disease that still can be found in Peru, specifically in some areas within the Peruvian Amazon jungle. Many times, the terminology used to describe relevant aspects of this disease is wrong, and some terms have been widely used since the middle ages. In this opinion article we will deal with three aspects in which both healthcare professionals and lay people continue using wrong terms and concepts.